Fiscal Impulse - Schinasi, Garry (IMF Working Papers; Working Paper, 1991)
The concept of fiscal impulse is defined, discussed, and differentiated from measures that attempt to summarize the macroeconomic effects of fiscal policy. Two methodologies are briefly discussed and their corresponding measures presented for the G-7 countries over the ten-year period ending in 1989. Controversies about the measure are highlighted and potential improvements are also discussed.